2007
DOI: 10.1128/iai.00638-06
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Proteomic Profiles of Group B Streptococcus Type V Reveal Potential Adherence Proteins Associated with High-Level Invasion

Abstract: Group B Streptococcus (GBS) is an opportunistic organism that can harmlessly colonize the human gut, vagina, and rectum but can also cause pneumonia, sepsis, and meningitis in neonates born to colonized mothers. We have shown previously that growth rate and oxygen level regulate the ability of GBS to invade eukaryotic cells in vitro. Herein we extend and expand on these observations to show that GBS type V, an emergent serotype, grown in a chemostat at a cell mass-doubling time (t d ) of 1.8 h with oxygen inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…These include proteins that bind to host cells, such as serine-rich repeat family proteins (32,50) and BibA (36), as well as proteins that bind specifically to components of host ECM, such as fibrinogen, fibronectin, and laminin (4,10,31,37,38,43,48). Some enzymes and transport binding proteins also have been suggested to be involved in GBS adherence through various mechanisms (16,22,27,29,47). GBS pili also have been shown to contribute to adherence, although recent work suggests that adherence and biofilm formation may be exclusively functions of PI-2a pili and not of PI-1 or PI-2b pili (30).…”
mentioning
confidence: 99%
“…These include proteins that bind to host cells, such as serine-rich repeat family proteins (32,50) and BibA (36), as well as proteins that bind specifically to components of host ECM, such as fibrinogen, fibronectin, and laminin (4,10,31,37,38,43,48). Some enzymes and transport binding proteins also have been suggested to be involved in GBS adherence through various mechanisms (16,22,27,29,47). GBS pili also have been shown to contribute to adherence, although recent work suggests that adherence and biofilm formation may be exclusively functions of PI-2a pili and not of PI-1 or PI-2b pili (30).…”
mentioning
confidence: 99%
“…Cell viability and count were determined by 0.4% trypan blue (Sigma) exclusion and hemocytometer counts as described (11). Spent medium was replaced every 2-3 days and 1 day before use.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in serotype distribution among various populations may also reflect differences in pathogenesis among the serotypes. Several promising vaccine candidates like capsular polysccharide (Cps); surface protein, such as ␣ and ␤ components of the C protein complex, Rib; surface immunogenic protein (Sip); and C5a peptidase have been identified to develop a vaccine against GBS and have been reviewed in detail recently (7)(8)(9)(10)(11). Despite the many studies that are focused on developing a GBS vaccine using conventional approaches, including the cultivation of pathogens and the identification of highly immunogenic and protective antigens using standard biochemical and microbiological techniques, little success has been achieved in terms of developing a vaccine that is globally effective (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical scenario concerning invasive diseases caused by GBS underlies the ability of this pathogen to bypass and/or injure endothelial cells to gain access to the blood stream. Previous studies demonstrated that the GBS-endothelial cell interaction process is a phenomenon of prime importance in the etiology of diseases caused by GBS, but an understanding of these events at the (7,8). Many factors that allow this microorganism to persist and thrive in human tissues remain unidentified.…”
Section: Introductionmentioning
confidence: 99%